Computer-Assisted Instruction for Elementary Accounting. - McKeown, James C. (The Accounting Review, 1976)
Abstract The article focuses on computer-assisted instruction (CAI) for elementary accounting. CAI materials for a two-semester elementary accounting course are being developed at the University of Illinois at Urbana-Champaign. The intent of the present paper is to report the progress of CAI, which has potential for great effectiveness in accounting education in anticipation of avoiding unnecessary duplication of costly effort in this area and to present results of a controlled experiment conducted during the Fall 1973 semester using the completed materials developed for the first semester, accounting principles course. One of the major advantages of materials developed in this project is their adaptability to improvement. This paper presents a discussion of objectives of the project, CAI system used, the approach taken and the experience to date in achievement of objectives. Objectives of the project, started in June 1972, include improvement of instruction in the elementary accounting sequence at the University of Illinois.